Simulation-Based Training Using A Novel Surabaya Hysterectomy Mannequin Following Video Demonstration To Improve Abdominal Hysterectomy Skills Of Obstetrics And Gynecology Residents During The COVID-19 Pandemic In Indonesia: A Pre- And Post-Intervention Study - Dara Dasawulansari Syamsuri, Dara
Abstract Purpose During the coronavirus disease 2019 (COVID-19) pandemic, the number of abdominal hysterectomy procedures decreased in Indonesia. The existing commercial abdominal hysterectomy simulation model is expensive and difficult to reuse. This study compared residents’ abdominal hysterectomy skills after simulation-based training using the Surabaya hysterectomy mannequin following a video demonstration.